(untitled) (Research, Society and Development, 2020)
The broiler production chain is productive, and chicken meat has achieved high export rates to several countries in the world. This study aimed to develop a mobile application that helps the producer to audit the issues of good production practices. The application was developed for Android and programmed in Java. For its development, questions were used, with different weights according to their importance for production. These questions were removed from the items that make up the manuals of good practices used in Brazil. A test was carried out with users to determine the possibility of using the application in the field. After answering all the questions, the user gets a score ranging from 5 to 1 (excellent to bad). It also indicates which questions they did agree with good practices. The test with users showed that the application was easy to understand and enabled users to make decisions that would improve broiler production.